مستحضرات التنظيف والتجميل في ميزان الشرع - بوكراع، صالح بن يحيى بن محمد (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2010)
This study aims to research the topic of: cosmetic and cleaning products, which are considered as the most popular consumer products and their industries as well. The study is focused on two main points: animal additives, and synthetic chemical additives. With animal additives, the study is concerned about their sources, as well as the rule of using them in cosmetic and cleaning product compositions. The study has researched the rule of utilization of impurities and taboos, and arrived at the conclusion that it is not allowed, except in cases of necessity and lack of other halal options, and the study has also discussed the issue of "Istihalah" and "Istihlak" and concluded that people cannot use them as a tool to use impurities and taboos, especially for accessories as it is with so many kinds of cosmetics. Regarding the use of synthetic chemical additives, the study has focused on the possible side effects that may be caused by those additives, and has come to a conclusion - which is under the light of the Jurisprudence bases, and the Shari´ah objectives - that use of these additives is not permissible if they contain any kind of harm on human health, but if the usage of these additives or cosmetics is not harmful as in the case of following certain instructions, the consumer then must follow those instructions. In the end, this study states that contemporary scholars must refer to specialists in order to come to the right decisions related to these emerging issues.